2021
DOI: 10.1186/s12877-021-02524-z
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting missed nursing care in hospitalized frail older adults in the medical wards: a qualitative study

Abstract: Background Frail older adults who are hospitalized, are more likely to experience missed nursing care (MNC) due to high care needs, communication problems, and complexity of nursing care. We conducted a qualitative study to examine the factors affecting MNC among hospitalized frail older adults in the medical units. Methods This qualitative study was carried using the conventional content analysis approach in three teaching hospitals. Semi-structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 44 publications
(3 reference statements)
0
19
0
Order By: Relevance
“…Different factors may affect the poor leadership of the ward managers, from the scarce training received to the consequences of high stress lived daily (e.g., Martella, 2021) resulting in burnout (Kelly & Hearld, 2020). However, also in previous studies, the inadequate leadership has been documented (e.g., Rezaei-Shahsavarloo et al, 2021) as aggravating the unfinished nursing care:…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Different factors may affect the poor leadership of the ward managers, from the scarce training received to the consequences of high stress lived daily (e.g., Martella, 2021) resulting in burnout (Kelly & Hearld, 2020). However, also in previous studies, the inadequate leadership has been documented (e.g., Rezaei-Shahsavarloo et al, 2021) as aggravating the unfinished nursing care:…”
Section: Discussionmentioning
confidence: 95%
“…However, two main new reasons have emerged: (a) the lack of nursing aides in their capacity to support nurses in concentrating their efforts on nursing care and (b) the quality of handovers in keeping priorities across shifts and teams. Also, at the nurses' level, some reasons have already been documented (increased age, education, experience and competencies, responsibility and motivation, stress and fatigue, time management skill, delegation skills, turnover, part time, time required for a nursing intervention and propensity to prevent legal/medicolegal issues; Arslan et al, 2022;Chiappinotto et al, 2022;Rezaei-Shahsavarloo et al, 2021). However, three elements seem to be new in this context: The progressive increase in the complexity and instability of patients, also due to their cognitive impairments (Rezaei-Shahsavarloo et al, 2021), triggers an additional demand for care: therefore, while on the one hand data should be continuously updated in the attempt to discover whether with the increased care demand the occurrence of unfinished nursing care will increase, and on the other more awareness should be devoted towards unfinished care, especially in the case of frail patients, in accordance with their increased risk of negative outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While a geriatric hospital might not be able to increase nurse:patient ratios, it would be able to change many of the factors affecting missed nursing care among frail older patients. In one study, researchers identified lack of managers’ competence in establishing care guidelines, negative attitudes towards frail older adults, weakness in interdisciplinary care and lack of knowledge, skills, and experience of nurses in dealing with frail older patients as reasons for missed nursing care ( Rezaei-Shassavarloo et al, 2021 ). These areas of concern are some of the strengths of many geriatric models of care ( Ellis et al, 2017 ; Van Creen et al, 2010 ; Baztán et al, 2009 ; Hshieh et al, 2015 ; Grigoryan et al, 2014 ).…”
Section: Geriatric Hospitals: Changing Typical Processes Of Care and ...mentioning
confidence: 99%
“…An architectural example of semicircular units within a geriatric hospital is seen in Figure 1. This structural design of a more efficient layout may help improve factors associated with missed nursing care by decreasing time spent walking between patient rooms in long hallways and increase time spent directly observing patients (Rezaei-Shahsavarloo et al, 2021). This open design may also assist efforts and improve attitudes towards reducing restraints (Gunawardena & Smithard, 2019).…”
Section: Developing Innovative Structural Designsmentioning
confidence: 99%